Evaluation of FNAC Thyroid Smears Using Bethesda System For Reporting Thyroid Cytopathology Nomenclature With Clinicopathological Correlation - Ansari, Shamim Ahmad; Malik, Reeni; Jain, Pramila (Annals of Pathology and Laboratory Medicine, 2023)
Background: The study aimed to interpret thyroid cytology by the Bethesda System for reporting thyroid cytology (TBSRTC) and to analyze the distribution of lesions under various diagnostic categories and subcategories. Methodology: This study was conducted as an observational study at tertiary care centre on patients with thyroid lesions. After history taking and detailed local, general and systemic examination, thyroid function tests were conducted. Apart from this, ultrasonography of lesion was done. Patients were subjected to FNAC and after fixation smears were stained with Papanicolaou stain. Results: About 53% thyroid lesions were hemorrhagic, followed by 17% blood mixed colloid and 4% colorless serous fluid. Sample adequacy was noted in 93.5% cases in our study. According to Bethesda system of classification, majority of lesions were benign (81.5%) whereas 6.5% lesions were unsatisfactory. Only 6% lesions were categorsied as malignant. Conclusion: FNAC is widely accepted as the most accurate, sensitive, specific, and cost- effective diagnostic procedure in the preoperative assessment of thyroid nodules. It is the first line of investigation and can differentiate benign nodules from malignant nodules of the thyroid in 95% cases. Applying a standard reporting system for thyroid cytology may enhance the communication between pathologists and clinicians, assists them to find out the rate of malignancy in each cytological group, and facilitating a more reliable approach for patient management.